Research on Fracture and Energy Evolution of Rock Containing Natural Fractures under Cyclic Loading Condition. (20th May 2021) - Li, Xueliang; Wang, Yu; Xu, Shuo; Yang, Haonan; Li, Bo
Abstract : For rock engineering in cold regions, the naturally fractured rock is susceptible to repeated freeze-thaw (F-T) weathering, coupled fatigue conditions of freeze-thaw (F-T), and stress disturbance act on rock mass, which can lead to the instability of rock engineering and even occurrence of geological hazards. Knowledge of how natural fracture affects the overall fracture evolution of freeze-thawed rock is crucial to rock mass stability. Laboratory multilevel cyclic loading tests are conducted to reveal the fatigue behavior and energy evolution for naturally fractured marble, as well as the influence of natural fracture volume on fracture evolution. The test results show that the preexisting natural fracture impacts fatigue strength, lifetime, and energy dissipation. The dissipated energy is correlated to all kinds of natural fracture (i.e., opening-mode, closing-mode, and filling-mode), and it decreases with the increase of the total natural fracture volume. The dissipated energy presents a first slow and then faster pattern as the cycle number grows. Compared with newly formed cracks, the proportion of energy consumed by stimulating natural cracks is smaller.